Dielectric behaviour and dechiralization lines dynamics of a pure Smectic-C* in confined geometry: onset of mesoscopic ferrielectricity. Issue 5 (8th April 2016) - Logbo, Harrod P.; Gagou, Yaovi; Dabrowski, Roman; Zurowska, Magdalena; Mettout, Bruno
ABSTRACT: Dielectric behaviour of a new ferroelectric liquid crystal (CLF08) having large spontaneous polarisation (120 nC/cm 2 at 110 Hz), short pitch and high purity, is studied in the frequency range 5 Hz to 1 MHz, in the smectic C* and smectic A phases using a 7-micron-thick cell in planar alignment. Dielectric permittivity, polarisation and optical measurements are investigated that shows complex ferroelectric behaviour. These experiments evidence the Goldstone and Soft mode relaxations far from the SmC*to SmA transition. The density of dechiralization lines is observed under polarised light microscope. Its behaviour under electric field exhibits a remarkable accordance with the dielectric response. These results are discussed in connection with a possible onset of ferrielectricity in the dechiralization lines system. GRAPHICAL ABSTRACT: